MEMBANGUN CACHE WEB PROXY MENGGUNAKAN MIKROTIK DI UNIVERSITAS INSTITUTE OF BUSINESS TIMOR LESTE - Sanches Cota, Cesar; Affandi, Luqman; Wahyu Widarti, Dinny (DINAMIKA DOTCOM, 2017)
Internet network is a basic requirement for people, companies, institutions, and government. In educational institutions, internet facility is very important, especially for the students to use the Internet to find references and information to strengthen insight. But the Internet network used in education instasi still many experience problems in accessing the internet, such as the University Institute Of Business Timor Leste who were having problems slow Internet network connection.The problem complicates the students and staff of the University Institute Of business access to the Internet to search for information or reference related to the learning process. Therefore, to overcome these problems to construction of a network system using a web proxy cache on Mikrotik RB951Ui-2HND configured to perform control access to Internet activities.Based on test results concluded that in building a web proxy cache using Mikrotik RB951Ui-2HND can solve the existing problems in the University Institute Of Business Timor Leste. Keywords: Cache, Mikrotik RouterBoard. Web Proxy